Generation 1.5 Learners : Removing the Mask of Student Invisibility and Recognising the Learning Disconnections That Marred Their Academic Journeys. - Serventy, Elizabeth; Allen, Bill (Student Success v.13 n.1 p.1-9 https://doi.org/10.5204/ssj.1867, 2022)
Distinctive cohorts of students revealing inherent problems in managing their learning are on-going concerns in all universities. Students identified as Generation 1.5 learners are an increasing phenomenon in Australian universities yet may be "invisible" or unknown to teaching staff. They are neither fully proficient in their first language nor in English which is typically their second language (L2). Characteristically possessing well-developed basic interpersonal communicative skills, they lack the cognitive academic learning proficiencies essential for tertiary success. This article reports on doctoral research into six Generation 1.5 undergraduates navigating one academic year in one Western Australian university. Key findings include their "invisibility" and how L2 learning "disconnections" marred their studies. Learning disconnections comprise discrepancies and disjunctions driven by the participants' immigration experiences, their academic needs, and their lack of connection with the teaching methods and the university-provided learning support services. Greater awareness of the distinctive features of these learners may improve their academic outcomes. [Author abstract]